Up-regulation of Minibrain/DYRK1A contributes to macrocephaly and brain overgrowth in a Drosophila model of fragile X syndrome - Mark Colt; Alicia Gordon; Yi-Jheng Peng; Ying Wu; Katherine Martin; Karen T. Chang (Proceedings of the National Academy of Sciences, 2026)
Fragile X syndrome (FXS) is the leading cause of inherited intellectual disability and autism. One common physical feature of FXS is macrocephaly, a condition typically associated with brain overgrowth and dysfunction; however, the mechanisms underlying its occurrence are unclear. Here, we uncover a role for the fragile X messenger ribonucleoprotein (FMRP) in regulating tissue growth through the Minibrain (Mnb) kinase, also known as DYRK1A, a gene up-regulated in Down syndrome and mutated in a specific form of autism. Using fly models of FXS, we find that Drosophila FMRP (dFmrp) suppresses the translation of Mnb. Loss of dFmrp leads to the up-regulation of Mnb in the developing brain, resulting in macrocephaly and brain enlargement. We find that brain overgrowth begins early in development and can be suppressed with DYRK1A inhibitors. At the cellular level, the Mnb/DYRK1A signaling pathway drives brain enlargement by inducing both neuronal hypertrophy and excessive proliferation of neural progenitors. We further demonstrate that Mnb up-regulates protein synthesis, and reducing Mnb activity or disrupting essential translational machinery restores brain size and improves locomotor coordination in the Drosophila FXS model. These data suggest that dysregulation of the Mnb/DYRK1A signaling pathway contributes to brain overgrowth and aberrant protein synthesis in FXS. More broadly, our findings highlight that neurodevelopmental disorders such as FXS, Down syndrome, and autism share disruptions in common molecular pathways.